Development of the Trauma-Related Anger Scale. (September 2019) - Sullivan, Connor; Jones, Russell T.; Hauenstein, Neil; White, Bradley
Anger is a pervasive problem following traumatic events. Previous research has demonstrated a moderate relationship between anger and posttraumatic stress disorder (PTSD), yet findings also highlight that anger has not been rigorously measured in the context of PTSD. Thus, this study concerns the development of a complimentary measure to assess anger in the context of PTSD. Participants were 435 undergraduate students. The participants were given a battery including the proposed scale and measures of trauma exposure, PTSD, anger, depression, anxiety, and social desirability. Exploratory factor analyses revealed a hierarchical, four-factor model provided the best fit to the data. The scale appeared psychometrically sound, with excellent internal consistency, good evidence of validity, and good model fit. This scale may provide implications for clinical work, specifically for the assessment and tracking of anger symptoms connected to PTSD. Additionally, this scale may assist with research by predicting treatment outcomes, aggression, and PTSD.